“Too Late For Action.” A.G. Huntsman, M.L. Fernald and the Belle Isle Strait Expedition of 1923 - Mills, Eric (Scientia Canadensis, 2020)
A. G. Huntsman’s Belle Isle Strait Expedition of 1923, the first oceanographic expedition organized by a Canadian, was modeled on the Canadian Fisheries Expedition of 1915, in which Huntsman had been a junior partner to the Norwegian fishery biologist Johan Hjort. Examination of Huntsman’s documents shows that the 1923 expedition had more than one aim. For example, Huntsman hoped that one of the participants would be M.L. Fernald, a botanist from Harvard University. Although Fernald did not take part, his reason for interest in the expedition was to document his hypothesis that the flora of northeastern North America had spread along an emergent borderland after the last glaciation or had remained in unglaciated areas. Huntsman’s aims were less transparent, but in addition to the oceanography they appear to be early steps in developing his concept of biapocrisis, the response of organisms as a whole to their individual environments, in which his collection of land plants during the expedition could play a part.